Evaluation of the Frequency of the Voice Signal as an Indicator of Sleepiness: A Study in Subjects with Sleep Deprivation - Segovia-Fernández, A (NEUROPSICOLOGIA CL, 2020)
The effects of drowsy driving have been identified as one of the causes of labor accidents.The need for non-invasive and accurate measurements has been a demand for many scientific disciplines ,among them, neuroscience and behaviour sciences.These specific disciplines can display evidence-based systems that might help prevent industrial and urban accidents.This research is an transnational, exploratory , pre experimental one .Its aim was to assess the voice signal as a drowsy driving indicator in sleep deprived individuals , in a controlled situation. Three individuals were sleep-deprived for 24 hours. The Epworth scale was applied to know the drowsiness degree the participants had before the study. Paragraphs were read, recorded and later analyzed along 7 measurement sessions using PRAAT voice software - The results obtained show evidence that drowsiness has an effect on the voice signal along time, enabling this method as a technologically efficient, non-invasive and low-cost alternative.